Perancangan Sistem Monitoring Penyelesaian Berkas Pidana Dengan Metode Rule Based Expert Systems dan Teknologi Radio Frequency Identification - Marfuah, Marfuah (JSINBIS (Jurnal Sistem Informasi Bisnis), 2017)
The process of criminal cases settlement is based on the regulation of time limit on trial. It is difficult to see the each stage of process because of the number of case files handled. To know the status of settlement, it needs monitoring system of RFID technology built by design to a model of Rule Based Expert Systems. It facilitates the process of data files so it can produce the right, quick and accurate report. The priority of criminal case files is based on the level of completion difficulty while the tracking involves 3 locations: police, public prosecutor and district court. Rule Based Expert System method works following an expert's knowledge in solving a problem. The design that has been made is capable of being implemented and according to the user’s needs. It helps to quickly generate the right information of criminal case settling time process.